2000
DOI: 10.1111/j.1469-7793.2000.t01-2-00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction by G‐proteins, Rho‐kinase and protein phosphatase to smooth muscle and non‐muscle myosin II

Abstract: We here review mechanisms that can regulate the activity of myosin II, in smooth muscle and non‐muscle cells, by modulating the Ca2+ sensitivity of myosin regulatory light chain (RLC) phosphorylation. The major mechanism of Ca2+ sensitization of smooth muscle contraction and non‐muscle cell motility is through inhibition of the smooth muscle myosin phosphatase (MLCP) that dephosphorylates the RLC in smooth muscle and non‐muscle. The active, GTP‐bound form of the small GTPase RhoA activates a serine/threonine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
1,022
2
12

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,118 publications
(1,053 citation statements)
references
References 95 publications
17
1,022
2
12
Order By: Relevance
“…3,4 MLCKcatalysed phosphorylation of MRLC is essential for the stimulation of myosin ATPase function and is involved in the control of various processes in normal cells such as contraction, motility, secretion, cytokinesis, and cytoskeletal remodeling. 2,3 Recently, it has been shown that MRLC phosphorylation also plays significant roles in malignant cells by regulating invasiveness and motility …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 MLCKcatalysed phosphorylation of MRLC is essential for the stimulation of myosin ATPase function and is involved in the control of various processes in normal cells such as contraction, motility, secretion, cytokinesis, and cytoskeletal remodeling. 2,3 Recently, it has been shown that MRLC phosphorylation also plays significant roles in malignant cells by regulating invasiveness and motility …”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation by MLCK on thr 18 and ser 19 has been shown to be critical for the activation of myosin ATPase activity and the contractile functions in smooth and nonmuscle cells. 3,4 Here, we report that MLCK-catalysed MRLC phosphorylation is also critical for the invasiveness of metastatic cancer cells. Inhibition of invasion was principally caused by impairment of cell motility, while adhesion to matrix and secretion of gelatinases were unaffected.…”
Section: Introductionmentioning
confidence: 93%
“…The phosphorylation of the myosin regulatory light chain (RLC) is essential for the formation of stress fibers originating from the interactions between myosin II and F-actin. It is known that the phosphorylation of RLC is complementarily regulated by two signaling pathways that involve (i) myosin light chain kinase (MLCK) and (ii) myosin light chain phosphatase (MLCP) [35][36][37]. LPA activates small GTPase RhoA via G-protein Each petri dish on which the fibroblasts were plated was filled with DMEM without FBS, and then was incubated for one night before the experiments were carried out.…”
Section: Biochemical Reagentsmentioning
confidence: 99%
“…Fig. 2 shows a temporal variation in the topographic and stiffness images of a fibroblast stimulated with 5 µM LPA, which served to increase cellular contractility [35][36][37]. The topographic images ( Figs.…”
Section: Effects Of the Cellular Contractility On The Stiffnessmentioning
confidence: 99%
“…This is thought to occur through regulatory mechanisms that involve calcium sensitizing. 59,60 Rho A, a G-protein, and its target Rho-kinase have been found to be involved with a-adrenergic (NE) and endothelin-1-stimulated smooth muscle contraction. This occurs through RK inhibition of MLC phosphatase.…”
Section: Ah and The Metabolic Syndromementioning
confidence: 99%